Investigation of voltage stability improvement in the distribution network with large amount of induction motors using PSS/E: Load interruption and use of SVCs - Bwembelo, Jagger Hamulili; Moreno Castillo, Sandra Milena (My University, 2014)
Voltage stability improvement methods following a disturbance and Fault Induced Delayed Voltage Recovery (FIDVR) event are studied with the aim of satisfying a voltage recovery criterion and saving as much load as possible. These methods are temporary load interruption and the use of Static Var Compensators (SVCs). The loads are temporarily tripped and then reconnected. The locations and sizes of SVCs are also determined. The criterion to be met is the recovery of voltages at all buses in the network to 0.9 pu within 1 s following a disturbance. Simulations are done on a typical distribution system with a large number of motor loads using Power System Simulator for Engineering (PSS/E) software with the help of Python programming language for automation and control and the results are analyzed. The results show that load interruption aids and significantly improves the voltage recovery following a disturbance in the network. It is also observed from the results that the use of SVCs also enables the voltage to recover faster with the criterion for voltage recovery at all buses fulfilled. However, the best results are obtained when load interruption is combined with the use of SVCs. The two methods complement each other. When the two methods are combined the amount of load that has to be interrupted is less and the number of SVCs required is also reduced. This results in fewer loads being interrupted. Moreover, the investment cost on SVCs is also reduced.
Keywords: Elkraftteknik; Electric power engineering